PENGGUNAAN FLAVID PADA PROCEDURE TEXT UNTUK MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRIS - Mutia Rahmah (Jurnal Didaktika Pendidikan Dasar, 2019)
One of the components of projected 21st-century education needed is 4C, i.e. critical thinking, creativity, collaborative, and communicative. The reality faced is students are very passive in English learning activities in the classroom. This shows that students' speaking skill is still low.  In addition, the learning is still dominated by the lecture method and individual tasks. With the aim of improving students' speaking skills, the teacher designs a combination of learning media between conventional and modern media namely Flavid (flashcard and video presentation). The purpose of this research is to find out how the use of Flavid on procedure text can improve the speaking ability of the students in Class IX-A of SMPN 2 Pelaihari. The results of this study are that the usage of flexible media in the learning process proved successful in improving students' speaking skills in English subjects. This can be seen based on the increase in the average value obtained by students from cycle I to cycle II. In the first cycle the number of students who has complete score is 7.41% and in the second cycle 74.07%. The ability to speak using Flavid media has increased by 66.66%.